Penguatan Sikap Kepemimpinan Dan Tanggung Jawab Dalam Pengelolaan Dana Kegiatan Sekolah - Raihan Dheka Amin Haryadi; Maria Angelica Dwi S; Suci Rahmawati (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
Vocational High Schools (SMK) play a crucial role in preparing students who possess not only technical competencies but also leadership character and a sense of responsibility. In school activities, students are often involved in committees and the management of activity funds; however, limited understanding of leadership and proper financial management is still commonly found. Therefore, this Community Service program aims to enhance leadership attitudes and responsibility among students of SMK Media Informatika Petukangan Selatan in managing school activity funds.The program employed an educational and participatory approach through material delivery, discussions, and simulations of simple school activity fund management. The results indicate an improvement in students’ understanding of leadership roles, responsibility, and basic skills in planning, utilizing, and reporting activity funds in a simple and accountable manner. This program is expected to contribute positively to students’ character development and to support the improvement of practical and contextual learning quality in the school environment.